Effects of a frozen elephant trunk on postoperative renal dysfunction in acute type A aortic dissection extending into the renal artery. Issue 10 (5th July 2022) - Okamura, Homare; Kitada, Yuichiro; Wada, Yohnosuke; Fujimori, Tomonari; Adachi, Hideo
Abstract: Background: We investigated the effects of frozen elephant trunk (FET) implantation on clinical outcomes in patients with acute type A aortic dissection (ATAAD) extending into the renal artery (RA). Methods: Between May 2016 and April 2021, 136 patients underwent surgery for ATAAD at our hospital. Patients who died within 7 days postoperatively and those without preoperative contrast‐enhanced computed tomography (CT) data were excluded from the study. The remaining 125 patients were included in this study. A preoperative CT‐documented RA abnormality was found in 53 patients. Clinical outcomes, including renal dysfunction and CT findings, were compared between 29 patients with and 24 patients without the FET prosthesis. Results: Among the 53 patients with RA abnormalities, origin of the RA from the false lumen was the most common type of abnormality. The percentage of men and rate of arch repair were higher, and the operation, cardiopulmonary bypass, and lower body hypothermic circulatory arrest times were longer in the FET than in the non‐FET group. Early mortality rates were similar between groups. The incidence of postoperative acute kidney injury (AKI) was lower in the FET group (35% vs. 67%, p = 0.028). Multivariable analysis showed that FET implantation was associated with a low incidence of AKI (odds ratio: 0.28, 95% confidence interval: 0.08−0.96; p = 0.043). Among the 125 patients with or without RA abnormalities, no predictor of AKI was identified. Conclusion: FET implantation protected against postoperative AKI in patients with ATAAD extension into the RA.